2015
DOI: 10.1093/ofid/ofv147
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies, Particularly B-Cell Lymphomas, Are a Frequent Cause of Mortality in Human Immunodeficiency Virus-1 Patients Despite Highly Active Antiretroviral Therapy

Abstract: Human immunodeficiency virus (HIV)-1-infected individuals are affected by diseases at rates above those of their HIV-negative peers despite the increased life expectancy of the highly active antiretroviral therapy era. We followed a cohort of approximately 2000 HIV-1-infected patients for 5 years. The most frequent cause of death in this HIV-1-infected cohort was malignancy, with 39% of all classified deaths due to cancer. Among the cancer deaths, B-cell lymphomas were the most commonly seen malignancy, repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…We evaluated comorbidities for association with 30-day readmission rates. The prevalence of malignancy in the HIV-1-infected population is significant and might impact readmission rates [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated comorbidities for association with 30-day readmission rates. The prevalence of malignancy in the HIV-1-infected population is significant and might impact readmission rates [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Riedel et al reported a high proportion of males and age <50 years in cases of HIV-related lymphomas [13]. According to Griffin et al , malignancies may develop even when HIV viral load is as low as <500 copies/ml [14]. In this scenario, one possible explanation could be a long period of high viremia prior to the development of the lymphoma or several periods with high viral loads contributing to lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, PWH have an increased risk of hematologic cancers [19][20][21]. B-cell aggressive NHL was included in the 1985 revised case definition of AIDS as one of three AIDS-defining cancer categories [3] and, currently, it is the most common hematological malignancy in PWH [22][23][24][25]. Nowadays, the most frequent types of lymphoma are DLBCL, decreasing from 63% in the pre-cART era (1986-1995) to 35-37% in the late-cART era (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015), and BL, increasing from 3% in the pre-cART era to 16-20% in the late-cART era [17].…”
Section: Epidemiologymentioning
confidence: 99%